Failure probability calculation model applied to gas pipelines - Frederico Carlos Maciel Thom; Geraldo Rossoni Sisquini; Matheus Jordão de Jesus; Oldrich Joel Romero (REM: International Engineering Journal)
Abstract This article presents an application for failure probability in long-pipeline gas systems through the development of trend curves over time for the attributes of corrosion wear, which are related to the length, width, and depth of the defect. In addition, Risk-Based Inspection (RBI) is applied in the most favorable numerical failure values according to the location of the defect, with the aim of analyzing the structural reliability and the expected useful life of the gas pipeline. To do this, it was necessary to use the data provided by pig readings in 2008, 2012 and 2018 by an instrumented pig, type Magnetic Flux Leakage (MFL), inspecting a gas pipeline with the finality to measure wall thickness. The 56 km long and 18 in diameter pipeline is partly onshore and partly offshore. Also, the pipeline anomalies are standardized according to the standards established in POF (2016). It is important to emphasize that the methodology described in this article can be used in the industry where the prevention of leakage incidents, the predictability of maintenance, and the elaboration of the respective inspection plans are required, since it has been theoretically possible to calculate the probability of failure in time beyond the respective impact on risk for the operational variables presented.